2014
DOI: 10.1007/s13277-014-2405-z
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR-513b inhibits cell proliferation, migration, and promotes apoptosis by targeting high mobility group-box 3 protein in gastric cancer

Abstract: The high mobility group-box 3 (HMGB3) protein belongs to the high mobility group box (HMG-box) subfamily, and recent studies have shown that HMGB3 is an oncogene for leukemia. HMGB3 is also expressed at a high level in the progression phase of breast and gastric cancer (GC). Using bioinformatic analyses, we found that HMGB3 is a potential target for miR-513b. However, the pathophysiological role of miR-513b and its relevance to the growth and development of GC have yet to be investigated. This study focuses on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…MiR-BART8-3p was highly expressed in our study, and it has been demonstrated to share seed sequences with miR-513b (Chen et al 2010). High mobility group-box 3 (HMGB3) is a potential target for miR-513b, which is an oncogene for leukemia and can promote cell proliferation (Chen et al 2014). It was speculated that miR-BART8-3p may act as a competitor to suppress the expression of miR-513b.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…MiR-BART8-3p was highly expressed in our study, and it has been demonstrated to share seed sequences with miR-513b (Chen et al 2010). High mobility group-box 3 (HMGB3) is a potential target for miR-513b, which is an oncogene for leukemia and can promote cell proliferation (Chen et al 2014). It was speculated that miR-BART8-3p may act as a competitor to suppress the expression of miR-513b.…”
Section: Discussionmentioning
confidence: 62%
“…When miR-513b is down-regulated, HMGB3 will be overexpressed. The elevated HMGB3 could promote EBVinfected CD8 + T cell proliferation, contributing to abnormal EBV-infected CD8 + T cell activation (Chen et al 2014). We propose that EBV-miRNA might influence immune functions of EBV-infected CD8 + T cells by sharing seed sequences with cellular miRNAs.…”
Section: Discussionmentioning
confidence: 91%
“…Luciferase activity was measured by the Dual-Luciferase Reporter Assay System (Promega). The ratios of TOP/FOP were calculated and used as indicators of WNT signaling activity [22]. …”
Section: Methodsmentioning
confidence: 99%
“…Another miRNA, miRNA-513b-5p, inhibits cell proliferation and migration and promotes apoptosis by targeting high-mobility group-box 3 protein (HMGB3) in gastric cancer (Chen et al 2014). With regard to PCOS, the apoptosis level is increased in the granulosa cells (Onalan et al 2005, Lin et al 2012; thus, we considered that the up-regulated miRNA-513b-5p in the PCOS cumulus cells might participate in the regulation of apoptosis with an impact on the atretic process of the follicles, leading to follicle maturation disorder.…”
Section: Discussionmentioning
confidence: 99%